Factor Structure and Internal Consistency on a Reduced Version of the Revised Test of Need for Cognitive Closure - Jaume, Luis Carlos; Schetsche, Christian; Roca, Marcelo Agustín; Quattrocchi, Paula (Frontiers in Psychology, 2022)
The need for cognitive closure is a construct postulated by Kruglanski that explains the motivational aspects that influence decision-making and its impact on the social environment. It was evaluated using a unidimensional scale criticized for its reliability and validity. Then, in response to the criticisms, Pierro and Kruglanski developed a new 14-item scale to measure two dimensions, which were not previously evaluated: urgency tendency and permanence tendency. Although the Revised Test of Need for Cognitive Closure is more economical in terms of assessment time, it would be optimal to develop a reduced test that can assess faster while maintaining validity and reliability. The present research aims to reduce the Revised Test of Need for Cognitive Closure scale to the Argentine context. To this end, we worked on a non-experimental design, assessing this scale within a sample of 690 Argentine university students (Women = 81.16%, Men = 18.84%), and proceeded to perform reliability, as well as confirmatory factor analysis, convergent validity, and factorial invariance analysis. The results indicate a bi-factorial structure of a Need for Cognitive Closure instrument with 8 items and two dimensions: urgency tendency (α = .76) and permanence tendency (α = .64), suggesting good reliability in both of them. In addition, a good convergent validity was demonstrated with other validated instruments, and finally, the factor loadings were shown to be invariant. In conclusion, the possibility of reducing the Revised Test of Need for Cognitive Closure, being a reliable and valid instrument, in our social environment is demonstrated.